2019
DOI: 10.3390/ma12223662
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Weld Bead Forming Rule during Double-Pulsed GMAW Process Based on Grey Relational Analysis

Abstract: Weld bead forming rule is very important during double-pulsed gas metal arc welding (DP-GMAW) process, and this process has more advantages than that of conventional arc welding process. This work employed grey rational analysis to explore the weld bead forming rule. Since the latest twinpulse XT DP control process was employed, the parameters adjustment was easier than that of conventional operation. The grey relational analyses between five main process parameters, which were average welding current, welding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…For gray relational analysis (GRA), GRA was adopted to identify the principal influential component in GCFs for the anti‐DR action. Gray relational grade (GRG) is applied to rank the impact of comparison sequence, which is obtained by calculating the distance between the comparison and reference series without any hypothesis on the distribution pattern [31] . The procedure was composed of 3 steps, including the establishment of gray relation, calculation of gray relational coefficient (GRC) and GRG.…”
Section: Methodsmentioning
confidence: 99%
“…For gray relational analysis (GRA), GRA was adopted to identify the principal influential component in GCFs for the anti‐DR action. Gray relational grade (GRG) is applied to rank the impact of comparison sequence, which is obtained by calculating the distance between the comparison and reference series without any hypothesis on the distribution pattern [31] . The procedure was composed of 3 steps, including the establishment of gray relation, calculation of gray relational coefficient (GRC) and GRG.…”
Section: Methodsmentioning
confidence: 99%
“…Yao, Zhou, Lin, Xu and Yue [14], through the double-pulsed GMAW technique, employed the grey relational based process to explore the weld bead forming rule and check the weld parameters effects, so a new method for the weld bead forming was set. Waqas, Qin, Xiong, Wang and Zheng [15] made an optimization of the effective area of deposition based on the GMAW additive manufacturing process parameters and the mechanical and microstructural of a multi-layer weld were analyzed.…”
Section: Iceubi2019mentioning
confidence: 99%
“…Liu et al [ 17 ] believed that increasing the base current amplitude or the thermal frequency of the current effectively enhanced the oscillation of the molten pool in the DP-GMAW of an AA6061-T6 aluminum alloy. Yao et al [ 18 ] explored the effect of a low frequency on DP-GMAW weld formation and proposed an empirical formula for the width of fish scales on the welding speed and low frequency. Mvola et al [ 19 ] reported that the improvement in the microstructure of DP-GMAW was due to the improved heat input and energy distribution by the current waveform control.…”
Section: Introductionmentioning
confidence: 99%